Mencari Bentuk Pengajaran Puisi untuk SMA di Tengah Masyarakat yang Tidak Butuh Puisi - Abdul Wachid (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
This paper is trying to look for form of poem instruction for high school in the middle of society that donâ€™t need poem. This is cumulative effect of capitalism, curriculum which minimal time for literary, low capability teacher, and oral society constraint. Here afforded alternative about the way teaching poem, among others by choosing poem which have been recognized by wide circle; if considering easy poem expression form comprehended by student, like ballad style and narrative, but donâ€™t too the length (follow the example of â€œGuerrillaâ€ poem from Rendra), and idea contained by that poem shall mount ably student; creating easy going atmosphere: donâ€™t first laden with technical problem, technical term like enjambment, typography, rhetoric medium.Â